Influence of laser versus lens-sparing vitrectomy on myopia in children with retinopathy of prematurity - Sumita Agarkar (Indian Journal of Ophthalmology, 2017)
Purpose: The purpose of this study is to compare the refractive error outcomes in the eyes of premature babies with retinopathy of prematurity (ROP) who underwent laser plus lens-sparing vitrectomy (LSV) in one eye and laser alone in the fellow eye. Methods: This is a retrospective study. Fourteen babies with Stage 4A of ROP or worse who underwent laser plus LSV in one eye (Group 1) and laser alone in the fellow eye (Group 2) were followed at 2 months, 6 months, 1 year, one and a half year, and 2 years. The main outcome variable studied was cycloplegic refraction at the baseline and follow-up visits. The change in spherical and cylindrical power at each visit was compared in Groups 1 and 2. The changes in spherical equivalent in subgroups were analyzed. Results: Mean gestational age at birth was 29.43 ± 2.10 weeks (range 26–32 weeks). Mean chronological age at the time of surgery was 4.11 ± 3.00 months (range 2–10 months). Mean postmenstrual age was 45.86 ± 12.13 weeks (range 39–75 weeks). Mean birth weight was 1340.71 ± 361.59 g (range 860–1980 g). All the babies in both groups had progressive myopia till 2 years follow-up; laser group had less myopia than LSV group till 1 year, thereafter, there was no difference in median till 2-year follow-up. The mean ± standard deviation of spherical equivalent in LSV versus laser group was: −4.36 ± 5.52 versus −3.21 ± 4.59 at 2 months; −5.09 ± 5.82 versus −4.04 ± 4.68 at 6 months; −7.14 ± 5.36 versus −5.36 ± 5.09 at 1 year; and −7.47 ± 1.38 versus −6.41 ± 1.91 at 2 years. Spherical equivalent difference across the visits did not differ significantly between Groups 1 and Group 2 in children whose birth weight was <1500 g (P = 0.247) and those who had more than 1500 g (P = 0.748), in those with gestational age between 20 and 30 weeks (P = 0.215) compared to those> 30 weeks (P = 0.602). Conclusion: No difference in the progression of myopia was noted in eyes that underwent additional LSV following laser photocoagulation in one eye and laser alone in the fellow eye.